Exploring Muhammadiyah Youth Interest in Agripreneurship Transformation in Sidenreng Rappang Regency: Insights from the Theory of Planned Behavior - Akbar; Aksal Mursalat; Muhammad Ikbal; Nining Triani Thamrin; Bahtiar Herman; Reza Asra (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2025)
Muhammadiyah youth have an excellent opportunity to be involved transforming of young agropreneurs in the agricultural sector by utilizing land assets. The purpose of this study is to explore the interest of Muhammadiyah youth in transforming into young agropreneurs in Sidenreng Rappang Regency using the Theory of Planned Behavior to analyze the influence of attitudes, subjective norms, and perceived behavioral control on intentions and behavior. Research methods include purposive sampling, observation, interviews, and Structural Equation Model (SEM) analysis with 100 respondents. The results showed that attitude directly and significantly influences behavior, while subjective norms and perceived behavioral control influence behavior through intention. The findings suggest that increasing positive attitudes and strengthening subjective norms are essential for forming solid intentions, increasing participation in agropreneurship. This research provides important insights for designing training programs and policies that support Muhammadiyah youth interest in the agricultural sector, which impacts the economic productivity and welfare of Muhammadiyah cadres in Sidenreng Rappang District.